A BACHELOR OF SOCIAL WORK PROGRAMME IN CANADA: ASSESSMENT OF NEED AND FEASIBILITY - L.T. Becker (European Scientific Journal, ESJ, 2014)
Social Service Worker students, both past and present, were surveyed to determine their interest in enrolling in a Bachelor of Social Work Progamme at Douglas College in British Columbia, Canada. Without a predictable catchment of students from the community it would be difficult for faculty and management at the college to justify funding the programme, designing new curriculum, hiring additional instructors, etc. Students were surveyed using a mixture of qualitative and quantitative measures over a period of approximately two months. Summary of the data met with positive results yet ongoing research challenges include developing curriculum for approval by college management and the Canadian Association of Social Workers, securing funding from the Ministry of Advanced Education, and hiring additional faculty. As part of its strategic plan the management at Douglas are committed to developing a college with the highest level of Bachelor level programmes offered in the province of British Columbia. As a research problem then it remains to be seen if the interest expressed by those surveyed will translate into the BSW actually being created and delivered.